“Chi Li 池莉.” - Kunze, Rui (2013)

Confucianism and Social Issues in China – the Academician Kang Xiaoguang: Investigations into NGOs in China, the Falun Gong, Chinese Reportage, and the Confucian Tradition. - Kunze, Rui (2011)

"Cooking Authenticity: Li Ziqi, Affective Labour, and China's Influencer Culture" - Kunze, Rui (Digital China: Creativity and Community in the Sinocybersphere, 2024)

“Cross-media, Cross-promotion: Intermediality and Cultural Entrepreneurism in Post-socialist China.” - Kunze, Rui (Concentric: Literary and Cultural Studies, 2017)

Displaced Fantasy: Pulp Science Fiction in the Early Reform Era of the People's Republic of China - Kunze, Rui (East Asian History, 2017)

Eileen Chang: Romancing Languages,Cultures and Genres. Modern Chinese Literature and Culture - Kunze, Rui (2013)

Envisioning the Flying Woman: Technology, Space, and Body in China's Print Culture (1911-1937) - Kunze, Rui (Comparative Literature and World Literature, 2021)

Fantasizing Science: the Idea of Progress in Early Chinese Science Fiction (1905-1920) - Kunze, Rui (Chinese Visions of Progress, 1895-1949, 2020)

“Female Subjectivity and Diasporic Experience: Zhao Shuxia’s Life and Fiction " - Kunze, Rui (2016)

"Governing Hunger: Numbers in the Promotion of the Sweet Potato in 1950s China." - Kunze, Rui (Twentieth-Century China, 2025)

Han Dong 韩东 - Kunze, Rui (2021)

Homey foods: Domesticating memories of the martial-law era in Taiwan's heritage tourism - Kunze, Rui (Memory Studies, 2024)

In the Heat of the Sun (Yángguãng Cànlàn De Rìzi, 1994) - Kunze, Rui (2022)
CRIS-Team Scopus Importer:2024-12-16

Karnevaleske Sprachpraxis chinesischer Netzbürger - Kunze, Rui (Sprache und Wirklichkeit in China, 2011)

Kexue - shijian - weilai: xin Zhongguo ertong kexue jiaoyu (1949-1966) 科學 - 實踐 - 未來：新中國兒童科學教育（1949-1966） - Kunze, Rui (二十一世紀 (Twenty-First Century), 2017)

Knowledge Production in Mao-Era China—Learning from the Masses - Matten, Marc; Kunze, Rui (Lexington, 2021)
This book traces and analyzes the transformation of the public discourse of science and technology in Mao-era China. Based on extensive primary sources such as science dissemination materials and technical handbooks, as well as mass media products of the Great Leap Forward and the Cultural Revolution periods, this book delineates the emergence of a pragmatic approach to knowledge in society. To achieve the goal of fast modernization with limited financial, human, and material resources, the party-state accommodated Western and local, "modern" and "traditional" knowledges in the fields of agricultural mechanization, steel production and Chinese veterinary medicine. The case studies demonstrate that scientific knowledge production in the Mao-era included various social groups and was entangled with political and cultural issues. This reveals and explains the continuity of scientific thinking across the historical divides of 1949 and 1978, which has hitherto been underestimated.

On the Spot: The Art of the Real at the Intersection of Poetry and Documentary - Kunze, Rui (Poetica, 2020)
Three documentaries on poetry appeared in China during a short period between 2014 and 2016, indicating a renewed interest in the real dimension of poetry, especially its "real" link with social and political issues. Despite the fact that they were made by very different cultural producers - state-owned China Central Television, independent filmmakers, and Youku, one of China's largest commercial video websites - these documentaries all deploy and appropriate the cultural discourse of xianchang.. (on the spot, live scene) to authenticate poet, poetic texts, poetic tradition, and poetic practices of writing, reading, and performing for political, social, aesthetic purposes. Approaching the intersection of poetry and documentary from the perspective of transmedia, this case study also explores destabilized criteria of poethood and evaluation, changing writing and reading practices as well as altered textuality of poems across media.
CRIS-Team WoS Importer:2020-10-23

Relocating "China" in Contemporary American Poetry: The Case of Timothy Yu - Kunze, Rui (Internationale Zeitschrift für Kulturkomparatistik, 2023)

“Stakes of Authentic Culinary Experience: Food Writing of Tang Lusun and Wang Zengqi.” - Kunze, Rui (Ex-position, 2020)

Struggle and symbiosis: the Canonization of the Poet Haizi and Cultural Discourses in Contemporary China - Kunze, Rui (Projekt Verlag, 2012)

"Tasting a Good Life: Narratives and Counter-Narratives of Happiness in the Documentary A Bite of China 2 (2014)." - Kunze, Rui (China Perspectives, 2018)

Topography of Red Memories in Modern China - Matten, Marc; Kunze, Rui (2021)
The establishment of sites of Red Tourism in contemporary China is a complex process involving different actors that range from the central government and the Central Committee of the Communist Party of China (CCP) to local and provincial state authorities and representatives of the tourism industry. Red Tourism sites are a combination of spaces for ideological education, leisure, and tourism development. Approaches in cultural geography have also pointed to the different functions of tourism, arguing that tourist sites are not only sites for passive consumption, or cultural appropriation but also produce a sense of place that can be crucial for generating identity and collective consciousness. This database provides an overview of the 800 sites of red tourism, their spatial distribution in the PRC, and their role in ideological education in contemporary China. <br

• “Trauma in Translation: Liao Yiwu’s ‘Massacre’ in English and German.” Chinese Poetry and Translation: Rights and Wrongs. Eds. Maghiel van Crevel and Lucas Klein. Amsterdam UP, 2019. 309-329. - Kunze, Rui (Chinese Poetry and Translation: Rights and Wrongs, 2019)

"Writing Workers in Post-Socialist China: Migrant Worker Poetry and Its New Left Reception." - Kunze, Rui (Oriens extremus, 2019)

Xiao Liu, Information Fantasies: Precarious Mediation in Postsocialist China (2019) - Kunze, Rui (2021)

《光影诗学》｜ 媒介间性中的抒情传统 - Kunze, Rui (2021)